EFECTO DEL TAMAÑO DEL GRUPO EN LA EXTENSIÓN DEL RANGO DE HOGAR DEL BÚHO DE SABANA (Speotyto cunicularia ): EVIDENCIA DE AUTORREGULACIÓN - Dussán, Salomé; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
This paper tests the hypothesis that a population of Savanna Owls (Speotyto cunicularia) . regulates its density through spacing behavior. We found a strong correlation between the number of individuals in a group and the distance to the nearest nest of another gro u p. However, in 50% of the cases the nearest nest was found to be empty. We discuss the implications of these results and propase sorne explanations based on classical population ecology theory.